Desenvolvimento e validação de método para determinação multiresíduo de agrotóxicos em urina empregando método QuEChERS e LC-MS/MS - Demarco, Marisa (2022)
Pesticides have been widely used in food crops to control pests, weeds, fungi, etc. The indiscriminate use of these organic compounds has contributed to the increase in cases of intoxication in humans, which can lead to more serious health problems, becoming a case of public health. Biological samples, such as urine, are more common and easy to collect, in addition to providing recent information on exposure to pesticides. In this sense, the use of methods that are capable of determining different classes and the largest number of compounds in a single procedure are of paramount importance to guarantee a more comprehensive result. Within this perspective, this work developed and validated a method for multiresidue determination of pesticides in urine using the unbuffered QuEChERS method and analysis by liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS). The parameters that influence the extraction efficiency were studied and after finding the best extraction conditions, the method was validated. The proposed procedure consisted of extracting 10 mL of urine (pH 5) with 2 mL of acetonitrile and the saltiong-out effect was achieved by adding 4 g of MgSO4 and 1 g of NaCl. Afterwards, a clean-up step was carried out using dispersive solid phase extraction, an aliquot the supernatant was transferred to a tube containing 150 mg of MgSO4, 25 mg of PSA and 25 mg of C18. Subsequently, the extract was diluted (1:4, v/v) in water, filtered (PTFE 0.22 µm) and injected into the chromatographic system. The unbuffered QuEChERS method was validated for 193 pesticides from different classes, proving to be selective and robust. Linearity was evaluated using matrix-fortified calibration from 0.5 to 20 µg L-¹ and showed r² > 0.99 for all evaluated compounds. LOQ ranged from 0.5 to 5 µg L-¹ (0.5 µg L-¹ for 177 compounds) and the LOD from 0.15 to 1.5 µg L-¹ with adequate accuracy (70 to 120%) and precision (RSD ≤20%). In the analysis of 50 urine samples collected from agricultural workers, residues of three neonicotinoids pesticides were detected with concentrations ranging from <LOQ to 4.43 µg L-¹ . Considering the results obtained, the use of the unbuffered QuEChERS method combined with LC-MS/MS detection allowed the determination of a wide range of analytes with high selectivity and sensitivity, proving to be efficient for multiresidue determination of pesticides in urine.